Pengaruh Citra Merek Dan Emosional Terhadap Kepuasan Konsumen Di Emilia Hotel Palembang - Veronia, Veronia; Juwita, Ratna (MDP Student Conference, 2024)
The purpose of this research was conducted to find out of brand image, service quality, emotional, and price on customer satisfaction at Emilia Hotel Palembang partially and simultaneously. Hotel Palembang partially and simultaneously. The sample from this research was 340 consumers who stayed at the Emilia Hotel Palembang. The research results stated that brand image and emotions had a positive and significant partial and simultaneous effect on consumer satisfaction.